2011
DOI: 10.1016/j.jcrs.2011.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ciliary sulcus diameter using ultrasound biomicroscopy in emmetropic eyes and myopic eyes

Abstract: Sulcus diameter measurements were most precise using UBM. The ciliary sulcus is vertically oval. The WTW diameter is not suitable for calculating a PC pIOL diameter, particularly in myopic eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 21 publications
2
48
1
Order By: Relevance
“…These results agree with some estimates of bias between horizontal WTW and STS estimates previously reported (bias -0.9mm), 19 but are completely contradictory of others (bias: 0.9mm; bias: 0.5mm; bias: 0.4mm). 2,18,24 This shows that there is very poor agreement between UBM devices in STS estimates (bias up to 1.2mm, 3 ICL sizes), highlighting the need for a conversion table between devices. (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results agree with some estimates of bias between horizontal WTW and STS estimates previously reported (bias -0.9mm), 19 but are completely contradictory of others (bias: 0.9mm; bias: 0.5mm; bias: 0.4mm). 2,18,24 This shows that there is very poor agreement between UBM devices in STS estimates (bias up to 1.2mm, 3 ICL sizes), highlighting the need for a conversion table between devices. (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…In this article we have attempted to estimate an appropriate error correction for all currently reported devices with the inclusion of a conversion table to be used in conjugation with the STAAR nomogram for ICL sizing. 0.24 (36) 0.47 (18) (36) 0.01 (37) 100 72 0.07…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the anterior segment of biometric parameters, e.g. horizontal corneal diameter (white-to-white, WTW), anterior chamber depth (ACD) [14] and ciliary sulcus-to-sulcus (STS) diameter [15,16], were correlated with the vault value. Kojima et al [17] reported that the distance between STS plane and anterior crystalline lens surface (STSL) was relevant to the vault value as well.…”
Section: Introductionmentioning
confidence: 99%